Determination of active ingredients in Chinese medicine Danning Tablets using dispersion solid-phase extraction by molecular imprinting nanomaterials coupled with HPLC-DAD. Issue 17 (25th April 2017) - Luo, Jieping; Chen, Ning; Yang, Zaiyue; Han, Jiyong; Zhu, Wanying; Hong, Junli; Zhou, Xuemin
Abstract : A reliable pretreatment method of magnetic molecularly imprinted polymers/dispersive solid-phase extraction was developed for selectivity and enrichment of targets. Abstract : A reliable method of magnetic molecularly imprinted polymers/dispersive solid-phase extraction (MMIPs-DSPE) was established for determination of polydatin (PD) and resveratrol (RSV) in Chinese medicine Danning Tablets® coupled with HPLC-DAD. This method was effectively used for the specific recognition and selective enrichment of target compounds and removal of matrix interferences in Chinese medicine. PD-MMIPs were obtained with PD as a template, methylacrylic acid (MAA) as a functional monomer, ethylene glycol dimethacrylate (EGDMA) as a crosslinking agent and azobisisobutyronitrile (AIBN) as an initiator. Good linearity was observed in the range of 0.01–10 μg mL −1, with the limit of detection of 2.5 ng mL −1 and 3.5 ng mL −1 for PD and RSV, respectively. The levels of PD and RSV in Danning Tablets® were found to be 769.94 μg g −1 and 130.03 μg g −1, and sample recoveries were between 91.79% and 102.23% with RSD < 6%.